2020
DOI: 10.3390/ma13235517
|View full text |Cite
|
Sign up to set email alerts
|

New Grain Formation by Constitutional Undercooling Due to Remelting of Segregated Microstructures during Powder Bed Fusion

Abstract: A microstructure has significant influence on the mechanical properties of parts. For isotropic properties, the formation of equiaxed microstructures by the nucleation of new grains during solidification is necessary. For conventional solidification processes, nucleation is well-understood. Regarding powder bed fusion, the repeated remelting of previous layers can cause nucleation under some conditions that are not explainable with classical theories. Here, we investigate this nucleation mechanism with an unpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…From Figure 2 , it is evident that, for both the as-built and heat-treated samples, new grains formed at the melt-pool border. As described in Rausch et al [ 24 ], new grains survive only at the flanks, when their orientation with respect to the local temperature gradient is better than the SX orientation (growth competition [ 38 ]). At the bottom, the SX is always better aligned, and new grains are overgrown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From Figure 2 , it is evident that, for both the as-built and heat-treated samples, new grains formed at the melt-pool border. As described in Rausch et al [ 24 ], new grains survive only at the flanks, when their orientation with respect to the local temperature gradient is better than the SX orientation (growth competition [ 38 ]). At the bottom, the SX is always better aligned, and new grains are overgrown.…”
Section: Discussionmentioning
confidence: 99%
“…In a former study, we investigated the nucleation mechanism for as-built samples in single-melt lines in single crystalline Inconel 718 [ 24 ]. We found that the inhomogeneous concentration distribution from segregation was effectively homogenized by convection in the melt pool.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations